Innovative Approaches for SME’s Sector - Cătălin Răzvan DOBREA; Florin ANGHEL (Revista de Management Comparat International)
Ensuring an adequate economic and social competitiveness level is a major priority of the SMEs on medium and long term. Success, in such a global competition, is conditioned by the degree of innovation and flexibility, by efforts in terms of financial, human and material resources and also by the effectiveness of their use. This paper presents a number of relevant issues in terms of implementing collaborative working environments in the SMEs work in order to enhance competitiveness at the microeconomic level.